Расчет статики кольцевых пластин методом рекуррентных соотношений - Данилов, В. Н. (НТУ "ХПИ", 2004)
In the article the problem solving which is offered describe a condition of a ring slice by a method of recurrent ratio. On the known tasks the advantages of this method as contrasted to by known methods are shown and the obtained outcomes are parsed. Capability of the solution of compound systems also is shown which comprise a ring slice.
Keywords: деформируемые структуры; задачи теории упругости; вектор состояния; составные оболочечные структуры; трубопроводные системы; конические оболочки